Aktivitas Tonikum Infusa Bunga Telang (Clitoria ternatea L.) terhadap Mencit dengan Metode Natatory Exhaustion dan Induksi Tidur - Eli Yuliana. H; Siwi Hastuti; Rahmat Hidayat (Journal of Innovative and Creativity, 2026)
ABSTRACT Tonics are agents that can stimulate body activity, thereby delaying feelings of fatigue, lethargy, and exhaustion. This study aimed to determine the ability of butterfly pea flower infusion to increase swimming time and its potential effect on the sleep duration of mice, as well as to evaluate the relationship between dose variation and tonic effects. Butterfly pea flower contains secondary metabolites such as alkaloids and flavonoids, which are known to produce tonic effects. This experimental study used 25 mice as test animals, divided into five groups. The test groups consisted of a negative control (distilled water), a positive control (caffeine 100 mg), and butterfly pea flower infusion at doses of 10%, 20%, and 40%. The results showed that butterfly pea flower infusion exhibited tonic effects in both the natatory exhaustion and sleep induction methods. The 10% dose produced tonic effects of 38.99% ± 10.34% in the natatory exhaustion method and 17.72% ± 6.13% in the sleep induction method. The 20% dose resulted in tonic effects of 52.82% ± 7.39% and 39.38% ± 6.22%, respectively. The 40% dose produced the greatest tonic effect, with values of 79.53% ± 3.82% in the natatory exhaustion method and 59.55% ± 1.72% in the sleep induction method. Keywords: Butterfly Pea Flower, Infusion, Natatory Exhaustion, Sleep Induction, Tonic